TROPHIC STRUCTURE OF AQUATIC INVERTEBRATES IN AMAZON FOREST STREAMS USING STABLE ISOTOPES - Ramos Pimentel, Diego; Martins Sousa, Ana Clara; Marques Couceiro, Sheyla Regina (Acta Biologica Brasiliensia, 2025)
The approach of stable isotopes has allowed to investigate the trophic structure in food webs and to determine the food source of the nutrient cycling pathways in terrestrial and aquatic ecosystems. Thus, the main objective of the present study was to investigate the trophic structure of macroinvertebrates in Amazonian streams. The research was carried out in 15 streams of the Alter do Chão Environmental Protection Area and surroundings, in Santarém-Pa city. A total of 3,150 individuals were collected, being 1,459 in the less rainy season and 1,691 in the rainy season, distributed in total in 65 taxa. The isotopic analysis was performed with 37 most representative taxa (57%), totaling 2,895 (92.57%) of the total number of individuals collected. We compared the isotopic analysis between the seasons (dry and rainy). In the less rainy season there were four trophic functional groups (herbivore, detritivore, omnivore and carnivore), while for the rainy season there were three groups (herbivore, detritivore, omnivore), with emphasis on the occurrence of herbivores in the rainy season. Most of the taxa collected showed a different isotopic signature between the two seasonal periods, changing the functional group, indicating food plasticity. The trophic classification currently used, based on studies in temperate areas, showed divergence largely with the results in the present work, based on stable isotopes. Trophic groups were related to abiotic variables such as temperature, dissolved oxygen, these variables being important for structuring the macroinvertebrate community, perhaps more important than the food source. Key words: ecosystems aquatic, isotopic analysis, trophic groups.